Simulation Techniques - Gammelgaard, Anders (DAIMI Report Series, 1991)
In the papers surveyed in this thesis a number of simulation techniques are presented together with their applications to several examples. The papers improve upon existing techniques and introduce new techniques. The improvement of existing techniques is motivated in programming methodology: It is demonstrated that existing techniques often introduce a double proof burden whereas the improved techniques alleviate such a burden. One application is to ensure delay insensitivity in a class of self-timed circuits. A major part of the thesis is concerned with the deduction and use of two simulation techniques to prove the correctness of translations from subsets of occam-2 to transputer code.